Real Time Implementation of Square Path Tracing by Autonomous Mobile Robot. Issue 1 (March 2021) - Das, Subhranil; Kumari, Rashmi
Abstract: Since last 30 years, autonomous mobile robot is one of the booming fields as well as in near future this field will be top research areas among various scientists and researchers since lot of recent technology have been changing frequently. In this paper, a small work has been executed by mobile robot for path tracing by using online robot simulator Robotsetup 1.0.13071. The simulation results have been displayed by tracing perfect square path by autonomous mobile robot which is advantageous to dense and cluttered environment by using this online simulator.